Dimensi sosial budaya atas pelayanan bidan-ibu hamil pada wilayah kerja Puskesmas Kalikotes Kabupaten Klaten Jawa tengah - MARIYAH, Emiliana (UGM., 2000)
The Indonesia government have made serious efforts already to provide antenatal, childbirth and postnatal care by midwife, but pregnant mother still ask dukun bersalin (tradtional curer) to help their childbirth, and maternal mortality was high compared with ASEAN countries. The information of medical for interaction of midwife and pregnant mother should be given in elucidation. It made pregnant mothers were able to overcome pregnancy problems. But the interaction of midwife and pregnant mother had certain problems about quality of antenatal care. This research was held on the work region of Kalikotes Puskesmas Induk (head of public health centre), district of Kalikotes, regency of Klaten in central Java. Case studies and longitudinal approach were used in this research. The data collecting applied a structured interview, depth interview, and participations a observation. Analyses w s ethnographycally and supported by frequencial distribution table and case t o case. The study said that they were: the lack of antenatal health care in meals pattern, time for taking a rest, a medicine, immunization, faith, and pregnancy concept. These cultural obstructions were resulted from: the low quality of the midwife tended not to give elucidation or suggestion. Because of that reason pregnant mother's knowledge of pregnancy interference and pregnancy was bgh risk. From that innovation indicated there was cognitive conflict in etiology problem and therapeutic. The cognitive conflict could be overcome by giving a knowledge of etiology and therapeutic through an approachment of explanatory models and dialogs. There was ignored suggestion or therapy from the midwife in case of meals pattern, time for taking a rest, taking a medicine, immunization, pregnancy problems caused by influence of social cultural dimension in faith, pregnancy concept, and the lack of knowledge of pregnant mother, her family, and her neighborhood. This study proved that system in faith and prohibition of pregnant mother remained strong. The causal factors were lack of effectiveness in elucidation and comprehension, as well as lack of interest in social cultural problems by implementer of program, and lack of faith from local community. It caused the acceptance of idea, the practice of pregnancy cares, and efforts of health behavior changes couldn't be reached satisfactorily. Suggested, that elucidation about therapy, and sign of childbirth would inform too, not only to pregnant mother, but her family, and neighborhood also. The explanation of elucidation was better audiovisually namely Zembar balik. In antenatal medical service program, emphasized that elucidation is necessary component in midwife-pregnant mother interaction, and midwife knowledge about f e r n would deepen. The interaction midwife-pregnant mother needs the familiarity and fhendliness of midwife. Village midwife dxtribution could be continued, because